2022
DOI: 10.1111/jvim.16482
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the urogenital microbiome in Miniature Schnauzers with and without calcium oxalate urolithiasis

Abstract: Background: Calcium oxalate (CaOx) uroliths are common in dogs. Humans with CaOx urolithiasis exhibit alterations of the urinary and urogenital microbiomes that might mediate urolith formation. Detection of urogenital microbes associated with CaOx in dogs could inform disease pathophysiology. Objective: To identify compositional differences in the urogenital microbiome of Miniature Schnauzers with and without CaOx uroliths. Animals: Nineteen midstream, voided urine samples from Miniature Schnauzers with (n = 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 109 publications
(191 reference statements)
0
7
0
Order By: Relevance
“…The involvement of the intestinal and urinary microbiota in the formation of calcium oxalate stone has been studied in humans [ 22 , 31 , 32 ], in rats [ 33 , 34 , 35 , 36 , 37 , 38 ], and in dogs [ 27 , 39 ], but not in cats. We hypothesized the following: (1) that mechanisms involving the microbiota, similar to those suspected in humans, might contribute to the formation of kidney calcium oxalate stones in cats, and (2) the use of antibiotics could lead to dysbiosis and thereby increase the risk of calcium oxalate stone formation.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of the intestinal and urinary microbiota in the formation of calcium oxalate stone has been studied in humans [ 22 , 31 , 32 ], in rats [ 33 , 34 , 35 , 36 , 37 , 38 ], and in dogs [ 27 , 39 ], but not in cats. We hypothesized the following: (1) that mechanisms involving the microbiota, similar to those suspected in humans, might contribute to the formation of kidney calcium oxalate stones in cats, and (2) the use of antibiotics could lead to dysbiosis and thereby increase the risk of calcium oxalate stone formation.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] However, few studies have examined the urinary microbiota of dogs via sequencing or culture, and even fewer have evaluated change over time. 4 15,18,[20][21][22][23][24] Multiple studies have reported that dogs and humans share microbes, including urinary tract pathogens. [25][26][27][28][29][30][31][32][33] Thus, characterizing healthy canine urinary microbiota and the associated resistance profiles over time is valuable both for canine health and has implications for One Health.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary tract commensals are thought to play a role in host health through immune stimulation, colonization resistance, and pathogen clearance 15‐19 . However, few studies have examined the urinary microbiota of dogs via sequencing or culture, and even fewer have evaluated change over time 15,18,20‐24 . Multiple studies report that dogs and humans share microbes, including urinary tract pathogens 25‐33 .…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] However, few studies have examined the urinary microbiota of dogs via sequencing or culture, and even fewer have evaluated change over time. 15,18,[20][21][22][23][24] Multiple studies report that dogs and humans share microbes, including urinary tract pathogens. [25][26][27][28][29][30][31][32][33] Thus, assessing the urinary microbiota of healthy dogs and the associated resistance profiles over time is valuable both for evaluating dog health and for assessing implications for human health.…”
mentioning
confidence: 99%